Struggles for democracy: strategies and resources of initiatives for non-citizen voting rights at local levels in Europe - Katrin Sontag; Metka Herzog; Silva Lässer (Comparative Migration Studies, 2022)
Abstract This paper deals with non-citizen voting rights from the perspective of grassroots initiatives that campaign for more inclusive local voting rights for migrants. It looks at three initiatives in three European cities with a growing foreign population: in Basel (Switzerland), Brussels (Belgium), and Freiburg (Germany). All three initiatives address authorities with the need to increase options for migrant political participation at the local level, encourage political engagement, and raise awareness of the topic. The initiatives use different strategies, which include the performance and appropriation of rights in symbolic elections or parliamentary sessions. We interpret these activities as “acts of citizenship” and observe that these acts are not only responses to available political opportunity structures, but rather mobilize external and internal networks and invest considerable resources to make this kind of engagement possible in a specific “resource environment”.